2010
DOI: 10.5194/amt-3-839-2010
|View full text |Cite
|
Sign up to set email alerts
|

Capability of multi-viewing-angle photo-polarimetric measurements for the simultaneous retrieval of aerosol and cloud properties

Abstract: Abstract. An important new challenge in the field of multiangle photo-polarimetric satellite remote sensing is the retrieval of aerosol properties under cloudy conditions. In this paper the possibility has been explored to perform a simultaneous retrieval of aerosol and cloud properties for partly cloudy scenes and for fully cloudy scenes where the aerosol layer is located above the cloud, using multi-angle photopolarimetric measurements. Also, for clear sky conditions a review is given of the capabilities of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 58 publications
3
59
2
Order By: Relevance
“…For some situations and parameters, additional viewing angles provide no improvement after a half dozen or so, while others (typically 25 those for which the observation system has marginal overall information content) do show improvements that eventually level off with many view angles. This is slightly lower than the conclusions of Hasekamp (2010), who found that sixteen viewing angles are sufficient for retrieval of most aerosol optical properties, and that the capability (for aerosols) with more viewing angles is constrained by the angle to angle measurement correlation present in most multi-angle imaging systems. While we do not account for observation correlation (unlikely in measurement systems such as ours) the difference is probably due to 30 our more constrained parameter space.…”
contrasting
confidence: 50%
See 1 more Smart Citation
“…For some situations and parameters, additional viewing angles provide no improvement after a half dozen or so, while others (typically 25 those for which the observation system has marginal overall information content) do show improvements that eventually level off with many view angles. This is slightly lower than the conclusions of Hasekamp (2010), who found that sixteen viewing angles are sufficient for retrieval of most aerosol optical properties, and that the capability (for aerosols) with more viewing angles is constrained by the angle to angle measurement correlation present in most multi-angle imaging systems. While we do not account for observation correlation (unlikely in measurement systems such as ours) the difference is probably due to 30 our more constrained parameter space.…”
contrasting
confidence: 50%
“…An interpretation of this could be that AOT is expressed smoothly and uniformly throughout the BRDF , and increasing the number of viewing angles does not add to the information about AOT in the overall measurement. Echoing other analyses, polarization improves the AOT uncertainty, especially over land (Hasekamp (2010); Hasekamp and Landgraf (2007); Knobelspiesse et al (2012)). …”
mentioning
confidence: 99%
“…the HARP -Hyper Angular Rainbow Polarimeter) have been developed for space applications and will be available for such measurements. We will also mention that polarization offers the possibility of retrieving aerosol information even in a pixel with subpixel clouds (Hasekamp, 2010), and there have been demonstrations of associations between aerosols and clouds that are sufficiently robust so that cloud effects in the aerosol product do not affect the conclusions of the analysis (Koren et al, 2010a).…”
Section: Suggested Satellite Observations Of Cloud Side Radiancesmentioning
confidence: 99%
“…More recent works also outlined the importance of polarization measurements for the retrieval of the aerosol properties in cloudy scenes. Hasekamp (2010) analyzed the contribution of multi-spectral, multi-angular total and polarized radiance measurements for the purpose of the simultaneous retrieval of the aerosol and cloud properties. Their study investigated various types of aerosolcloud-contaminated scenes (AAC scenes and scenes with fractional cloud cover mixed with aerosols).…”
Section: F Waquet Et Al: Retrieval Of Aerosol Microphysical and Optmentioning
confidence: 99%